Strategi Komunikasi dalam Mengatasi Keluhan Pelanggan: Studi Kasus PT. Namto Kraf Indo - Firdaus, Achmad; Mirza, Mochammad; Fournawati, Sri Murdilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze communication strategies in dealing with customer complaints at a company called PT. Namto Kraf Indo. Handling complaints is a crucial part of the business world that can have a big impact if not resolved quickly. Therefore, an effective communication strategy is needed so that complaints can be resolved immediately. This research uses a qualitative approach with a case study method. Data collected through observation, in-depth interviews and documentation of workers, managers and other related divisions. Data analysis was carried out using descriptive qualitative analysis techniques to identify forms of communication strategies carried out by the company and to look for factors inhibiting the communication process in the company. The results of the research show that the communication strategy used by the Namto company is not completely good, it needs to continue to be developed by improving the quality of the workforce so that it is better able to compete with other companies and it needs to hold gradual job training for employees so that they are able to have additional skills to support better service capacity. good for the company. Researchers suggest the need for a more intense evaluation, this is useful so that companies know where the capacity of their workers is and how to improve it to help the company compete with other companies in terms of service and quality of its workforce.